Stage-Wrights : Shakespeare, Jonson, Middleton, and the Making of Theatrical Value - Yachnin, Paul Edward, 1953- (Book collections on Project MUSE., 1997)
To many of their contemporaries, William Shakespeare, Ben Jonson, and Thomas Middleton were little more than artisanal craftsmen, "stage-wrights" who wrote plays for money, to be performed in common play-houses and in a manner of the antithetical to what Jonson himself viewed as the higher calling of poetry. In response to the conflicting pressures of censorship and commercialism, Paul Yachnin contends, players and dramatists alike had promulgated the idea of drama's irrelevance, creating a recreational theater that failed to influence its audience in any purposeful way. In Stage-Wrights Yachnin shows how Shakespeare, Jonson, and Middleton struggled to reclaim not only the importance of their art, but their own social legitimacy as well through the reshaping of the commercial theater. His bold readings of their works unveil the strategies by which they sought power from their privileged but powerless position on the margins. Adopting a hermeneutical approach, he explores a wide range of historical evidence to describe how English Renaissance drama depicted the world in ways refracted by the interests of the playing companies; throughout, he challenges recent historicist models that have overrated the importance of dramatic productions to society and its institutions of authority